Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Kinerja Keuangan dengan Peringkat Kinerja Lingkungan sebagai Variabel Moderasi - Oktaviani Ari Wardhaningrum; Anggreda Ratih Swastika Devi; Dewi Ayu Puspita (InFestasi, 2022)
This study aims to analyze the effect of corporate social responsibility on financial performance with environmental performance ratings as a moderating variable. The sample in this study is a company listed in the Sri – Kehati Index of Indonesian Stock Exchange in 2017 – 2020. This study is quantitative research. The data used is a secondary data of the company’s financial statement and company sustainability reports. Based on sampling technique with purposive sampling, there are 13 companies. Data collection techniques use documentation techniques for financial statement and sustainability report that are published on the Indonesian Stock Exchange website and the company’s website. The analysis technique used is moderated regression analysis. The results of this study show that corporate social responsibility has a positive effect on the company's financial performance and environmental performance ratings are able to moderate the effect of CSR disclosure on financial performance of companies